Atmospheric forcing of rapid marine-terminating glacier retreat in the Canadian Arctic Archipelago - Cook, Alison J.; Copland, Luke; Noël, Brice P. Y.; Stokes, Chris R.; Bentley, Michael J.; Sharp, Martin J.; Bingham, Robert G.; van den Broeke, Michiel R. (Université d'Ottawa | University of Ottawa, 2019)
The Canadian Arctic Archipelago contains >300 glaciers that terminate in the ocean, but little is known about changes in their frontal positions in response to recent changes in the ocean-climate system. Here, we examine changes in glacier frontal positions since the 1950s and investigate the relative influence of oceanic temperature versus atmospheric temperature. Over 94% of glaciers retreated between 1958 and 2015, with a region-wide trend of gradual retreat before ~2000, followed by a fivefold increase in retreat rates up to 2015. Retreat patterns show no correlation with changes in subsurface ocean temperatures, in clear contrast to the dominance of ocean forcing in western Greenland and elsewhere. Rather, significant correlations with surface melt indicate that increased atmospheric temperature has been the primary driver of the acceleration in marine-terminating glacier frontal retreat in this region.